Method for manufacturing laminated battery and apparatus for manufacturing laminated battery
The conductive bent part is formed by contacting the welding part of the laminated film, and cracks are detected by the conduction confirmation unit, which solves the problem of cracking of the protective resin layer in the laminated battery manufacturing and ensures battery quality.
Patent Information
- Application Number
- CN202410288895.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-21
- Filing Date
- 2024-03-14
- Publication Date
- 2024-12-24
AI Technical Summary
During the manufacturing process of the laminated battery, the flexion of the welding portion causes cracks in the protective resin layer, especially on the trough side and the trough side in the bent portion, which is difficult to detect, resulting in failure of the defective battery. Excluded before shipment.
The conductive bent member is used to contact the welded portion of the laminated film to form a bent portion at an angle of 90° or less, and the cracks in the bent portion are detected by the conduction confirmation unit to ensure battery quality.
Effectively detect and remove cracks in the protective resin layer, ensure the quality of the stacked battery shipped, and avoid battery defects caused by cracks.
Smart Images

Figure CN119181904A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for manufacturing a stacked battery and an apparatus for manufacturing a stacked battery. Background Art
[0002] In a laminated battery in which an electrode body is covered with a laminate film, a portion of the laminate film is welded to form a welded portion in order to seal the electrode body. Furthermore, the welded portion is bent in order to improve the structural efficiency of the battery.
[0003] For example, Japanese Patent Publication No. 2019-200973 discloses a method for manufacturing a secondary battery, which is a method for manufacturing a secondary battery having a folded portion at at least one end in an outer body subjected to a lamination process, comprising: a process of bringing a pressing plate into contact with a base point of the folding of the end of the outer body; after the contact process, sliding the pressing plate and a pushing plate arranged at a position opposite to the pressing plate in a manner of clamping the end, bending the end around the base point, and clamping the end with the pressing plate and the pushing plate to form the folded portion, wherein the surface of the pushing plate that slides with the end has an inclined surface for bending the end and a clamping surface for clamping the end, and the inclined surface is inclined in the cross-section orthogonal to the width direction of the pushing plate, and the cross-sectional area of the pushing plate is inclined in a manner that becomes narrower in the sliding direction, and the inclined surface is inclined in the width direction. Summary of the invention
[0004] When the welded portion of a laminated film is bent at an angle of less than 90° to form a bent portion, cracks may sometimes occur in the protective resin layer of the laminated film. Furthermore, the occurrence of such cracks may sometimes also occur in the protective resin layer on the mountain fold side of the bent portion, and may be particularly prominent in the protective resin layer on the valley fold side of the bent portion. Therefore, there is a need for a manufacturing method and a manufacturing device for a laminated battery, which are capable of detecting the occurrence of cracks in the protective resin layer on the valley fold side and the mountain fold side of the bent portion, thereby enabling laminated batteries having cracks in the protective resin layer (i.e., defective laminated batteries) to be removed before shipment.
[0005] The present disclosure has been made in view of the above-mentioned actual situation, and an object of the present disclosure is to provide a method and apparatus for manufacturing a laminated battery capable of detecting the presence or absence of cracks in a protective resin layer in a bent portion of a weld.
[0006] <1> A method for manufacturing a stacked battery, wherein the stacked battery comprises an electrode body and a stacked film covering and sealing the electrode body, the stacked film having a structure in which at least a metal layer and a protective resin layer on the outside of the metal layer are stacked, the stacked film having a fusion portion in which the ends overlap each other and the inner surfaces are fused together, the manufacturing method comprising a bending step, wherein a bending member is brought into contact with the fusion portion and is bent into an angle or an arc at an angle of less than 90° to form one or more bends, the bending member being made of a conductive material, and the bending step being a step of performing the bending while confirming the conduction between the bending member and the metal layer of the stacked film.
[0007] <2> The method for manufacturing a laminated battery according to <1>, wherein the folding member is a fulcrum member that contacts as a fulcrum a valley fold side of the curved portion of the laminated film.
[0008] <3> A method for manufacturing a stacked battery according to <1> or <2>, wherein the bending step is the following step: configuring a bending roller as the bending member, moving the stacked battery in a direction along the rotation of the bending roller, and contacting the fusion portion in the stacked film to form the bent portion.
[0009] <4> The method for manufacturing a stacked battery according to <3>, wherein the bending process is the following process: a plurality of the bending rollers are arranged in the moving direction of the stacked battery, and the plurality of the bending rollers are sequentially brought into contact with the welding portion in the stacked film while the stacked battery is moved to form the bent portion, and the bending is performed while at least confirming the conduction between the bending roller that has last contacted the bent portion and the metal layer of the stacked film.
[0010] <5> A manufacturing device for a stacked battery, wherein the stacked battery has an electrode body and a stacked film covering and sealing the electrode body, the stacked film having a structure in which at least a metal layer and a protective resin layer on the outside of the metal layer are stacked, the stacked film having a welding portion in which the ends overlap each other and the inner surfaces are welded together, the manufacturing device comprising: a bending member made of a conductive material, which is in contact with the welding portion and is bent into an angle or an arc at an angle of 90° or less to form a bent portion; and a conduction confirmation unit connected to the bending member and the metal layer of the stacked film, and confirms the conduction between the bending member and the metal layer.
[0011] According to the present disclosure, it is possible to provide a method for manufacturing a laminated battery and an apparatus for manufacturing a laminated battery capable of detecting the presence or absence of cracks in a protective resin layer in a bent portion of a weld. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described below with reference to the accompanying drawings, wherein like reference numerals represent like elements, and wherein:
[0013] Figure 1 A schematic cross-sectional view illustrating a stacked battery manufactured using the stacked battery manufacturing method and manufacturing apparatus according to the present embodiment;
[0014] Figure 2 A schematic cross-sectional view illustrating a bending step of forming a bent portion in a method of manufacturing a stacked battery according to the present embodiment and an apparatus for manufacturing a stacked battery that forms a bent portion;
[0015] Figure 3 for Figure 2 , which is a schematic cross-sectional view illustrating a state in which cracks have occurred in the protective resin layer; and
[0016] Figure 4 This is a schematic cross-sectional view showing an example of a solid battery. DETAILED DESCRIPTION
[0017] Method and device for manufacturing laminated battery
[0018] The manufacturing method of a stacked battery involved in an embodiment of the present disclosure is a manufacturing method for a stacked battery, wherein the stacked battery has an electrode body and a stacked film that covers and seals the electrode body inside, the stacked film has a structure in which at least a metal layer and a protective resin layer on the outside of the metal layer are stacked, and the stacked film has a welding portion in which the end portions overlap each other and the inner surfaces are welded.
[0019] The manufacturing method of the laminated battery includes a bending step, wherein a bending member is brought into contact with a welded portion and bent into an angle or an arc shape at an angle of 90° or less to form one or more bent portions. The bending member is made of a conductive material. In the bending step, the bending is performed while confirming the conduction between the bending member and the metal layer of the laminated film.
[0020] The manufacturing device of the stacked battery involved in the embodiment of the present disclosure is a manufacturing device for manufacturing the stacked battery, wherein the stacked battery has an electrode body and a stacked film that covers and seals the electrode body inside, the stacked film has a structure in which at least a metal layer and a protective resin layer on the outside of the metal layer are stacked, and the stacked film has a welding portion that overlaps the end portions with each other and welds the inner surfaces.
[0021] The manufacturing device of the stacked battery comprises: a bending member made of a conductive material, which contacts the welding part and is bent into an angle or an arc at an angle of less than 90° to form a bent part; and a conduction confirmation unit connected to the bending member and the metal layer of the stacked film to confirm the conduction between the bending member and the metal layer.
[0022] Hereinafter, one embodiment of a method and apparatus for manufacturing a laminated battery according to the present disclosure will be described with reference to the drawings.
[0023] Each of the following drawings is a schematic diagram, and the size and shape of each part are appropriately exaggerated for easier understanding.
[0024] Figure 1 The following is a schematic cross-sectional view illustrating a stacked battery manufactured using the stacked battery manufacturing method and manufacturing apparatus according to the present embodiment.
[0025] Figure 1 The laminated battery 10 shown has an electrode body 2 and a laminate film 4 covering and sealing the electrode body 2. The laminate film 4 has a welded portion 40 in which the ends are overlapped and the inner surfaces are welded. The welded portion 40 has a bent portion 40a bent into an angle or an arc shape at an angle of 90° or less.
[0026] Here, the bending process for forming the bent portion 40a and the manufacturing apparatus for the laminated battery for forming the bent portion 40a are used. Figure 2 Provide explanation.
[0027] At once Figure 2 As for the welded portion 40 shown, the ends of the laminated film 4 are overlapped with each other and the inner surfaces are welded, that is, one end 4u and the other end 4d of the laminated film 4 are overlapped. The one end 4u and the other end 4d of the laminated film 4 have a three-layer structure in which metal layers 44u, 44d, protective resin layers 42u, 42d on the outside of the metal layers 44u, 44d, and welding resin layers 46u, 46d on the inside of the metal layers 44u, 44d are stacked.
[0028] exist Figure 2 In the embodiment, the folding roller 6 as a folding member contacts the protective resin layer 42u on the side of one end 4u of the laminated film 4 in the welded portion 40, and folds the laminated film 40 at an angle of 90° or less with the contact point of the folding roller 6 as a fulcrum, thereby forming a bent portion 40a. That is, the folding roller 6 is a fulcrum member that contacts the valley fold side in the bent portion 40a as a fulcrum. In addition, the folding roller 6 is bent toward the laminated film 4 at the contact point with the laminated film 4. Figure 2 The stacked battery having the welded portion 40 rotates in the direction of rotation of the folding roller 6, that is, toward the front side. Figure 2The bending roller 6 is moved toward the front side of the bending portion 40, so that the bending roller 6 contacts the moving welded portion 40, thereby forming the bent portion 40a. Although not shown in the figure, the opposing member (e.g., the opposing roller) as the bending member may be moved toward the mountain fold side ( Figure 2 The lower side of the weld portion 40 is in contact.
[0029] Figure 2 The manufacturing apparatus of the stacked battery shown in the figure has an ammeter 8 as a conduction confirmation unit. As for the ammeter 8, the bending roller 6 as a bending member and the metal layer 44u on the one end 4u side of the stacked film 4 are connected by wires 82 and 84. In addition, the metal layer 44u on the one end 4u side of the stacked film 4 is connected to the wire 82, so it becomes a partially exposed form.
[0030] Here, a conventional method and apparatus for manufacturing a laminated battery will be described.
[0031] When the welded portion of the laminated film is bent at an angle of 90° or less to form a bent portion, cracks may sometimes occur in the protective resin layer of the laminated film. It is believed that this is cracking caused by stress concentration at the bent portion of the protective resin layer due to bending. In addition, the occurrence of such cracks may sometimes occur in the protective resin layer on the mountain fold side of the bent portion, and is particularly prominent in the protective resin layer on the valley fold side of the bent portion. It is believed that this is because stress is more likely to be concentrated on the valley fold side, and the bent members abut against each other, so that cracks are likely to occur starting from the contact position.
[0032] In addition, when cracks occur in the protective resin layer on the valley side of the curved portion, it is difficult to distinguish the presence or absence of cracks, and the smaller the angle of the bend in the curved portion (that is, the more acute the angle becomes), the more difficult it is to distinguish the cracks. However, in a laminated film that is a thin film, it is difficult to detect cracks by non-destructive inspection such as X-ray inspection.
[0033] Therefore, there is a need for a method and apparatus for manufacturing a laminated battery that can detect the occurrence of cracks in the protective resin layer on the valley fold side and the mountain fold side of a bent portion.
[0034] In this embodiment, if Figure 2 As shown, as a conduction confirmation unit, an ammeter 8 is provided, which is connected to the bending roller 6 and the metal layer 44u as the bending member to confirm the conduction between the bending roller 6 and the metal layer 44u. Then, the bending is performed while confirming the conduction between the bending roller 6 and the metal layer 44u using the ammeter 8. The protective resin layer 42u on the one end 4u side of the laminated film 4 has no cracks (i.e., Figure 2 In the state shown in FIG. 4 , the bending roller 6 and the metal layer 44u are not in contact, and it is confirmed that there is no electrical conduction. However, if Figure 3 As shown, cracks 420 are generated in the protective resin layer 42u on the side of one end 4u of the laminated film 4, and the bending roller 6 is in contact with the metal layer 44u, and electrical conduction is confirmed in the ammeter 8. Thus, in this embodiment, electrical conduction is confirmed when cracks are generated in the protective resin layer, so the presence or absence of cracks in the protective resin layer in the laminated film of the manufactured laminated battery can be confirmed. As a result, laminated batteries with cracks in the protective resin layer (i.e., defective laminated batteries) can be removed before shipment.
[0035] Furthermore, in Figure 2 In the figure, as a conduction confirmation unit, a bending roller 6 as a bending member connected to the ammeter 8 is shown as a fulcrum member that contacts as a fulcrum on the valley fold side in the curved portion 40a of the weld 40. However, this is not limited to this, and the bending member (for example, a bending roller) connected to the conduction confirmation unit may be brought into contact with the mountain fold side in the curved portion of the weld. In this case, it is possible to detect the presence or absence of cracks in the protective resin layer on the mountain fold side in the curved portion of the weld. In addition, the bending member (for example, a bending roller) connected to the conduction confirmation unit may be brought into contact with both the valley fold side and the mountain fold side in the curved portion of the weld. In this case, it is possible to detect the presence or absence of cracks in the protective resin layer on the mountain fold side and the protective resin layer on the valley fold side in the curved portion of the weld.
[0036] In an embodiment of the present disclosure, a plurality of folding rollers may be arranged in the moving direction of the stacked battery, and the stacked battery may be moved while the plurality of folding rollers sequentially contact the welded portion in the stacked film to perform folding, thereby forming a bent portion. In this case, it is preferred that the folding bend be performed while at least one side confirms the conduction between the folding roller that last contacts the bent portion and the metal layer of the stacked film. By confirming the conduction between the folding roller that last contacts the bent portion and the metal layer of the stacked film, cracks generated before the folding roller contacts the bent portion can also be detected.
[0037] The number of bends in the weld is 1 or more, and there may be 2 or more bends. The angle in the bend of the weld may be 90° or less, and may be an acute angle compared to 90°, or the angle of the bend may be 0° (i.e., a bend in a shape where the weld is bent 180°). The bend has a shape that is bent into an angle or an arc. An angle means a shape having an angle, and an arc means a curved shape without an angle.
[0038] As a flexural member, Figure 2A bending roller is shown in the figure, but it is not limited to this. For example, as a bending member, a plate-like member serving as a fulcrum member may be brought into contact on the valley fold side of the bending portion, a block-like pressing member may be brought into contact on the mountain fold side of the bending portion, and a bending may be performed. At least a part of the bending member is made of a conductive material. Specifically, at least a part of the welding portion is made of a conductive material in such a manner that the portion in contact with the protective resin layer (that is, the portion in contact with the metal layer inside the protective resin layer when cracks are generated in the protective resin layer) and the portion connected to the conduction confirmation unit are electrically conductive. The bending member may be made of a conductive material as a whole. Examples of conductive materials include metals.
[0039] As a conduction confirmation unit, Figure 2 Although an ammeter is shown in FIG. 1 , the present invention is not limited to this, and any means capable of confirming electrical continuity, such as a voltmeter and a resistance measuring device, may be used.
[0040] Battery components
[0041] Next, the electrode body and the laminated film constituting the laminated battery manufactured by the laminated battery manufacturing method and manufacturing apparatus according to the present embodiment will be described.
[0042] (1) Laminated film
[0043] The laminated film has a structure in which at least a metal layer and a protective resin layer on the outside of the metal layer are laminated. Alternatively, the laminated film may be a three-layered film further having a fusion resin layer on the inside of the metal layer.
[0044] As the material of the welding resin layer, for example, olefin resins such as polypropylene (PP) and polyethylene (PE) can be listed. As the material of the metal layer, for example, aluminum, aluminum alloy, and stainless steel can be listed. As the material of the protective resin layer, for example, polyethylene terephthalate (PET) and nylon can be listed. The thickness of the welding resin layer is, for example, greater than 40 μm and less than 100 μm. The thickness of the metal layer is, for example, greater than 30 μm and less than 60 μm. The thickness of the protective resin layer is, for example, greater than 20 μm and less than 60 μm. The thickness of the entire laminated film is, for example, greater than 70 μm and less than 220 μm.
[0045] (2) Electrode body
[0046] The electrode body functions as a power generation element of the battery and generally has a positive electrode current collector, a positive electrode active material layer, an electrolyte layer, a negative electrode active material layer, and a negative electrode current collector in this order in the thickness direction.
[0047] The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material layer may further contain at least one of a conductive material, an electrolyte, and a binder. The shape of the positive electrode active material is, for example, a particle shape. As the positive electrode active material, for example, an oxide active material can be cited. In addition, sulfur (S) can be used as the positive electrode active material.
[0048] As the positive electrode active material, preferably a lithium composite oxide is included. The lithium composite oxide may contain at least one selected from F, Cl, N, S, Br and I. In addition, the lithium composite oxide may have a crystal structure belonging to at least one space group selected from space groups R-3m, Immm, and P63-mmc (also referred to as P63mc, P6 / mmc.). In addition, the main arrangement of transition metals, oxygen and lithium in the lithium composite oxide may be an O2 type structure.
[0049] Examples of lithium composite oxides having a crystal structure belonging to R-3m include Li x Me y O α X β (Me represents at least one selected from Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si and P, X represents at least one selected from F, Cl, N, S, Br and I, and satisfies 0.5≤x≤1.5, 0.5≤y≤1.0, 1≤α<2, 0<β≤1) represented by a compound.
[0050] Examples of lithium composite oxides having a crystal structure belonging to Immm include Li x1 M 1 A 1 2(satisfying 1.5≤x1≤2.3, M 1 Contains at least one selected from Ni, Co, Mn, Cu and Fe, A 1 Contains at least oxygen, A 1 The ratio of oxygen in the composite oxide is 85 atomic % or more) (as a specific example, Li2NiO2), Li x1 M 1A 1-x2 M 1B x2 O 2-y A 2 y (0≤x2≤0.5, 0≤y≤0.3, at least one of x2 and y is not 0, M 1A represents at least one selected from Ni, Co, Mn, Cu and Fe, M 1Brepresents at least one selected from the group consisting of Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta and W, A 2 represents a composite oxide represented by at least one selected from F, Cl, Br, S and P).
[0051] Examples of lithium composite oxides having a crystal structure belonging to P63-mmc include: x M2 y A composite oxide represented by O2 (M1 represents an alkali metal (preferably at least one of Na and K), M2 represents a transition metal (preferably at least one selected from Mn, Ni, Co and Fe), and x+y satisfies 0<x+y≤2).
[0052] Examples of lithium composite oxides having an O2 type structure include Li x [Li α (Mn a Co b M c ) 1-α ]O2 (0.5<x<1.1, 0.1<α<0.33, 0.17<a<0.93, 0.03<b<0.50, 0.04<c<0.33, M represents at least one selected from Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W and Bi) represented by a composite oxide, as a specific example, Li 0.744 [Li 0.145 Mn 0.625 Co 0.115 Ni 0.115 ]O2, etc.
[0053] In addition, the positive electrode preferably contains a solid electrolyte selected from the solid electrolyte group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte in addition to the positive electrode active material, and more preferably at least a portion of the surface of the positive electrode active material is coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. As the halide solid electrolyte that covers at least a portion of the surface of the positive electrode active material, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5) [LTAF electrolyte].
[0054] As the conductive material, for example, carbon materials can be listed. The electrolyte can be a solid electrolyte or a liquid electrolyte. The solid electrolyte can be an organic solid electrolyte such as a gel electrolyte, or an inorganic solid electrolyte such as an oxide solid electrolyte or a sulfide solid electrolyte. In addition, the liquid electrolyte (electrolyte) contains, for example, a supporting salt such as LiPF6 and a solvent such as a carbonate solvent. In addition, as the adhesive, for example, a rubber adhesive and a fluoride adhesive can be listed.
[0055] The negative electrode active material layer contains at least a negative electrode active material. The negative electrode active material layer may further contain at least one of a conductive material, an electrolyte, and a binder. Examples of the negative electrode active material include metal active materials such as Li and Si, carbon active materials such as graphite, and Li4Ti5O 12 The negative electrode current collector may be in the form of a foil or a mesh. The conductive material, electrolyte, and binder are the same as those described above.
[0056] The electrolyte layer is disposed between the positive electrode active material layer and the negative electrode active material layer and contains at least an electrolyte. The electrolyte may be a solid electrolyte or a liquid electrolyte. As the electrolyte layer, a solid electrolyte layer is preferred. The electrolyte layer may have a separator.
[0057] The solid electrolyte preferably contains at least one solid electrolyte species selected from the solid electrolyte group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, and a halide solid electrolyte.
[0058] As a sulfide solid electrolyte, it is preferred to contain sulfur (S) as the main component of the anion element, and it is more preferred to contain, for example, Li element, A element and S element. The A element is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In. The sulfide solid electrolyte may further contain at least one of O and a halogen element. As a halogen element (X), for example, F, Cl, Br, I and the like can be listed. There is no particular limitation on the composition of the sulfide solid electrolyte, for example, xLi2S·(100-x)P2S5(70≤x≤80), yLiI·zLiBr·(100-yz)(xLi2S·(1-x)P2S5)(0.7≤x≤0.8, 0≤y≤30, 0≤z≤30) can be listed. The sulfide solid electrolyte may have a composition represented by the following general formula (1).
[0059] Li 4-x Ge 1-x P x S4(0<x<1)···Formula (1)
[0060] In formula (1), at least a portion of Ge may be replaced by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. In addition, at least a portion of P may be replaced by at least one selected from Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V and Nb. A portion of Li may be replaced by at least one selected from Na, K, Mg, Ca and Zn. A portion of S may be replaced by a halogen. The halogen is at least one of F, Cl, Br and I.
[0061] As an oxide solid electrolyte, it is preferred to contain oxygen (O) as the main component of the anion element, for example, it may contain Li, Q element (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W and S), and O. As oxide solid electrolytes, garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON-type solid electrolytes, Li-PO-based solid electrolytes, Li-BO-based solid electrolytes, etc. can be listed. As garnet-type solid electrolytes, for example, Li7La3Zr2O 12 , Li 7-x La3(Zr 2-x Nb x ) 12 (0≤x≤2), Li5La3Nb2O 12 Etc. As perovskite-type solid electrolytes, for example, (Li, La)TiO3, (Li, La)NbO3, (Li, Sr)(Ta, Zr)O3, etc. can be cited. As NASICON-type solid electrolytes, for example, Li(Al, Ti)(PO4)3, Li(Al, Ga)(PO4)3, etc. can be cited. As Li-PO-based solid electrolytes, Li3PO4 and LIPON (compounds in which a part of O in Li3PO4 is replaced by N) can be cited. As Li-BO-based solid electrolytes, Li3BO3 and compounds in which a part of O in Li3BO3 is replaced by C can be cited.
[0062] As the halide solid electrolyte, a solid electrolyte containing Li, M and X is preferred (M represents at least one of Ti, Al and Y, and X represents F, Cl or Br). Specifically, Li 6-3z Y z X6 (X represents Cl or Br, z satisfies 0<z<2), Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5). Li 6-3z Y zAmong X6, Li3YX6 (X represents Cl or Br) is more preferred in terms of excellent lithium ion conductivity, and Li3YCl6 is more preferred. 6-(4-x)b (Ti 1-x Al x ) b F6 (0<x<1, 0<b≤1.5) is preferably contained together with a solid electrolyte such as a sulfide solid electrolyte from the viewpoint of suppressing oxidative decomposition of the sulfide solid electrolyte, for example.
[0063] The positive electrode current collector collects current from the positive electrode active material layer. Examples of the positive electrode current collector include stainless steel, aluminum, nickel, iron, titanium, carbon, etc., preferably aluminum alloy foil or aluminum foil. Aluminum alloy foil and aluminum foil can be made using powder. The shape of the positive electrode current collector is, for example, foil-shaped or mesh-shaped.
[0064] The negative electrode current collector collects current from the negative electrode active material layer. Examples of the material of the negative electrode current collector include metals such as copper, SUS, and nickel. Examples of the shape of the negative electrode current collector include foil and mesh.
[0065] Battery structure
[0066] The structure of a solid battery has a stacked structure of positive electrode / solid electrolyte layer / negative electrode. Among solid batteries, there are so-called all-solid batteries that use solid electrolytes as electrolytes. The solid electrolyte may contain less than 10% by mass of electrolyte relative to the total amount of electrolyte. Furthermore, the solid electrolyte may be a composite solid electrolyte containing an inorganic solid electrolyte and a polymer electrolyte.
[0067] The positive electrode has a positive electrode active material layer and a current collector, and the negative electrode has a negative electrode active material layer and a current collector.
[0068] The solid electrolyte layer may have a single-layer structure or a multi-layer structure of two or more layers.
[0069] Solid state batteries may have, for example, Figure 4 The cross-sectional structure shown in FIG. 1 is a solid electrolyte layer B. Figure 4 That is a 2-layer structure. Figure 4 This is a schematic cross-sectional view illustrating an example of a solid state battery. Figure 4 The solid battery shown has a negative electrode including a negative electrode collector 113 and a negative electrode active material layer A, a solid electrolyte layer B, and a positive electrode including a positive electrode collector 115 and a positive electrode active material layer C. The negative electrode active material layer A includes a negative electrode active material 101, a conductive auxiliary agent 105, and a binder 109. The positive electrode active material layer C includes a coated positive electrode active material 103, a conductive auxiliary agent 107, and a binder 111, and the coated positive electrode active material 103 is a positive electrode active material whose surface is coated with an LTAF electrolyte or a LiNbO3 electrolyte.
[0070] In addition, the solid battery can be formed by sealing the stacked end faces (side faces) of the stacked structure of the positive electrode / solid electrolyte layer / negative electrode with resin. The current collector of the electrode can be configured with a buffer layer, an elastic layer, or a Positive Temperature Coefficient (PTC) thermistor layer on the surface.
[0071] Battery
[0072] The laminated battery in the present disclosure is typically a lithium-ion secondary battery. As the use of the battery, for example, power sources for vehicles such as hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), battery electric vehicles (BEV), gasoline vehicles, and diesel vehicles can be cited. It is particularly preferred to be used as a driving power source for hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV) or battery electric vehicles (BEV). In addition, the battery in the present disclosure can be used as a power source for mobile bodies other than vehicles (such as railways, ships, and aircraft), and can also be used as a power source for electrical products such as information processing devices.
[0073] The present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any configuration having substantially the same structure and achieving the same function and effect as the technical concept described in the patent claims of the present disclosure is included in the technical scope of the present disclosure.
Claims
1. A method for producing a stacked battery, wherein: The laminated battery comprises an electrode body and a laminated film covering and sealing the electrode body, wherein the laminated film has a structure in which at least a metal layer and a protective resin layer on the outside of the metal layer are laminated, and the laminated film has a welded portion in which the ends are overlapped and the inner surfaces are welded together. The manufacturing method includes a bending step, wherein a bending member is brought into contact with the welded portion and bent into an angle or an arc shape at an angle of 90° or less to form one or more bent portions. The bending member is made of a conductive material. The bending step is a step of performing bending while confirming electrical continuity between the bending member and the metal layer of the laminate film.
2. The method for manufacturing a stacked battery according to claim 1, wherein: The folding member is a fulcrum member that contacts as a fulcrum the valley fold side of the curved portion of the laminated film.
3. The method for manufacturing a stacked battery according to claim 1, wherein: The folding step is a step of providing a folding roller as the folding member, and bringing the folding roller into contact with the welded portion in the laminate film while moving the laminated battery in a direction along the rotation of the folding roller to form the bent portion.
4. The method for manufacturing a stacked battery according to claim 3, wherein: The bending process is as follows: a plurality of bending rollers are arranged in the moving direction of the stacked battery, and the plurality of bending rollers are sequentially contacted with the welding part in the stacked film while the stacked battery is moved to form the bent part, and the bending is performed while at least confirming the conduction between the bending roller that finally contacts the bent part and the metal layer of the stacked film.
5. A manufacturing device for a stacked battery, wherein: The laminated battery comprises an electrode body and a laminated film covering and sealing the electrode body, wherein the laminated film has a structure in which at least a metal layer and a protective resin layer on the outside of the metal layer are laminated, and the laminated film has a welded portion in which the ends are overlapped and the inner surfaces are welded together. The manufacturing device comprises: A bending member made of a conductive material, which contacts the welded portion and is bent into an angle or an arc shape to form a bent portion at an angle of 90° or less; and A conduction confirmation unit is connected to the bending member and the metal layer of the laminate film and is configured to confirm conduction between the bending member and the metal layer.
